2007
DOI: 10.1088/0957-4484/18/19/195602
|View full text |Cite
|
Sign up to set email alerts
|

Controlled low-temperature fabrication of ZnO nanopillars with a wet-chemical approach

Abstract: Aqueous chemical growth (ACG) is an efficient way to generate wafer-scale and densely packed arrays of ZnO nanopillars on various substrate materials. ACG is a low-temperature growth approach that is only weakly influenced by the substrate and even allows growth on flexible polymer substrates or on conducting materials. The advanced fabrication of wafer-scale and highly vertically aligned arrays of ZnO nanopillars on various substrate materials is demonstrated. Moreover, it is possible to control the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Experiments have shown that due to depletion of Zn 2+ ions the growth of the ZnO nanowires normally slowed down with time and eventually arrived at growth-dissolution equilibrium for longer reaction times. This limitation can be overcome by adding additional Zn nitrate solution [79], or by replenishing the growth solution [77,78,80]. Under the mediation of NH 3 ·H 2 O, however, Zn 2+ could be stabilized through the reversible reaction shown in equation (8) below, thus, leading to a relatively low level of supersaturation being maintained in the solution.…”
Section: Nano Resmentioning
confidence: 99%
“…Experiments have shown that due to depletion of Zn 2+ ions the growth of the ZnO nanowires normally slowed down with time and eventually arrived at growth-dissolution equilibrium for longer reaction times. This limitation can be overcome by adding additional Zn nitrate solution [79], or by replenishing the growth solution [77,78,80]. Under the mediation of NH 3 ·H 2 O, however, Zn 2+ could be stabilized through the reversible reaction shown in equation (8) below, thus, leading to a relatively low level of supersaturation being maintained in the solution.…”
Section: Nano Resmentioning
confidence: 99%
“…It has been reported that both the length and diameter of the ZnO nanorods increased with the reaction time in the hydrothermal growth method [14,15]. It was noticed from the SEM images that in 0.025 M zinc nitrate hydrate growth solution, the 6 h grown ZnO nanorods were distributed uniformly with an average diameter of about 170 nm and an average length of about 2 µm.…”
Section: Resultsmentioning
confidence: 95%
“…During growth the expected pH value might be between 6.5 and 7. 111 The produced Zn(OH)2 is thermodynamically unstable and it would be dehydrated when it is incorporated into the crystal, therefore could be referred as a growth unit. 55 Before the substrates were placed into the solution, and to prepare contact pads for the electrochemical measurements, a small part of the Au coated glass was covered.…”
Section: Preparation Of Zno Co3o4 and Bivo4 Seed Solutionsmentioning
confidence: 99%